2021
DOI: 10.37934/arfmts.89.2.4355
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer of MHD Dusty Nanofluid Toward Moving Plate with Convective Boundary Condition

Abstract: This paper considers the flow and heat transfer characteristics of dusty nanofluid over a moving plate in the presence of magnetohydrodynamic (MHD) with convective boundary condition. Two types of nanofluid namely CuO-water and Al2O3-water permeated with dust particles are considered. The governing partial differential equations are converted into a system of non-linear ordinary differential equations using similarity transformation, then the non-linear ordinary differential equations are solved using shooting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, Rubaa'i et al, [6] who studied the effect of non-uniform heat source/sink on the hybrid nanofluid mixed convection flow over a stretching sheet concluded the concentration of the chosen nanoparticles significantly contributed to the enhancement of heat transfer rate. Meanwhile, Low et al, [7] investigated the heat transfer characteristics of dusty nanofluid over a moving plate in the presence of MHD with convective boundary condition. The comparative analysis between copperoxide (CuO) and aluminium oxide (Al 2 O 3 ) -water dusty nanofluid showed that the increasing of the volume fraction of nanoparticles and volume fraction in dust particles significantly enhanced the temperature profiles of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rubaa'i et al, [6] who studied the effect of non-uniform heat source/sink on the hybrid nanofluid mixed convection flow over a stretching sheet concluded the concentration of the chosen nanoparticles significantly contributed to the enhancement of heat transfer rate. Meanwhile, Low et al, [7] investigated the heat transfer characteristics of dusty nanofluid over a moving plate in the presence of MHD with convective boundary condition. The comparative analysis between copperoxide (CuO) and aluminium oxide (Al 2 O 3 ) -water dusty nanofluid showed that the increasing of the volume fraction of nanoparticles and volume fraction in dust particles significantly enhanced the temperature profiles of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, dual solutions which are upper and lower solutions have been detected and successfully proven for certain range of mixed convection parameter. On the other hand, Low et al, [14] who explored the dusty nanofluid flow with the presence of magnetic field concluded that an increase in Biot number which represented the influence of convective boundary condition on the fluid flow has improved the flow temperature, consequently enhanced the heat transfer rate. They also observed that the magnetic field parameter has a tendency to create an opposing force to the flow, lowering the velocity boundary layer while increasing the heat boundary layer.…”
Section: Introductionmentioning
confidence: 99%

Falkner-Skan Flow of Nanofluid with Convective Boundary Condition

Nurul Diana Mohammad,
Nur Ilyana Kamis,
Mohamad Hidayad Ahmad Kamal
et al. 2024
ARNHT